A constraint on the x dependence of the light antiquarks ratio - Steffens, F. M. (Elsevier B.V., 2002)
We perform a careful study on the effect of the Pauli blocking to the light antiquark structure of the proton sea. We develop the formal expressions for the antiquark distributions, highlighting the role played by quark statistics and the vacuum structure. Ratios involving the antiquarks are calculated. In particular, it is found that Delta(d) over bar (x)/Delta(u) over bar (x) should be negative and x independent. (C) 2002 Elsevier B.V. B.V. All rights reserved.